Review: Synthesis of rGO in Its Use as Thin Films with Various Polymer Matrices - Rahma Alya Hidayah; Nenni Mona Aruan; Nur Aini Fauziyah; Reffany Choiru Rizkiarna; Alfriana Margareta (Faraday: Journal of Fundamental Physics, Research, and Applied Science, 2026)
Reduced graphene oxide (rGO) is a two-dimensional carbon material that has been widely developed as a functional filler in polymer-based thin films due to its high surface area, good electrical conductivity, and adequate interface compatibility. This article presents a literature review on the synthesis of rGO and its use as thin films with various polymer matrices, namely polyaniline (PANi), poly(vinylidene fluoride) (PVDF), poly(vinylidene fluoride–trifluoroethylene) [P(VDF-TrFE)], and chitosan. The review was conducted on open access scientific articles discussing rGO synthesis methods, thin film fabrication techniques, and structural, morphological, thermal, and electrical characterization of composite materials. The results of the study show that rGO can improve the functional performance of polymer thin films through the formation of conductive networks, strengthening of interface interactions, and crystal nucleation effects. In the PANi matrix, rGO increases electrical conductivity and stability, while in PVDF and P(VDF-TrFE), rGO promotes the formation of electroactive crystalline phases that enhance piezoelectric properties. Meanwhile, in chitosan, strong interfacial interactions improve electrochemical response and the potential for environmentally friendly sensor applications.